Resolving Bank Failures in Argentina : Recent Developments and Issues - de la Torre, Augusto (World Bank, Washington, DC, 2015)
Policies and procedures to resolve bank failures have evolved significantly in Argentina since the introduction of currency convertibility in 1991, and particularly in reaction to the 1995 tequila crisis, which exposed the inadequacy of the bank exit framework in place then. The author reviews the institutional changes introduced in Argentina in 1995 to handle bank failures more effectively, particularly the creation of the deposit guarantee scheme and the procedural framework for resolving bank failures, embedded in Article 35 of the Financial Institutions Law. This framework enables the Central Bank to carve out the assets and privileged liabilities of the failing bank and transfer them to sound banks, thereby sending only a residual balance sheet to judicial liquidation. Subsequent refinements in the application of Article 35 procedures eventually led to current Argentine practice. The author examines this practice in detail by considering the handling of the recent failure of Banco Almafuerte. The author assesses a number of issues that arise from the Argentine model of bank failure resolution, taking into account both country-specific circumstances and more general concepts and concerns. He emphasizes the potential tradeoffs between reducing contagion risk, limiting moral hazard, and avoiding unnecessary destruction of asset value; the implications of priority-of-claims rules and least-cost criteria; the pros and cons of alternative organizational and institutional arrangements; and the need for legal security. Finally, he outlines two prototypical approaches to striking a balance between rules and discretion, an issue underlying much of the ongoing policy discussion on alternative bank exit frameworks.